The Effect of World Oil Prices, Gold Prices, and Other Energy Prices on the Indonesian Mining Sector with Exchange Rate of Indonesian Rupiah as the Moderating Effect - Ady, Sri Utami (International Journal of Energy Economics and Policy, 2021)
The paper aimed to determine the effect of world oil prices, gold prices, and other energy prices on the Indonesian mining sector with the moderating influence of the exchange rate of the Indonesian Rupiah. This study is quantitative in which the data gathered from Investing.com from 2016 to 2020. The variables considered in the survey include exchange rate, Indonesian stock returns of mining companies, gold prices, oil prices, and gasoline prices. Concerning the analysis, the vector autoregression, Augmented Dickey-Fuller (ADF), and adopt the granger causality test. The results of this study identified no effect of oil price, gasoline price, and gold price on the Indonesian stock exchange of mining companies. On the other hand, there is no moderation of foreign exchange of Indonesian Rupiah among the relationship of oil price, gasoline price, and gold price with stock returns of Indonesian mining companies. This study's results are restricted to the Indonesian context, and the data considered from 2016 to 2019. Keywords: Exchange rate, Oil price, Gold price, Gasoline price, Indonesian Mining Sector Stock Returns. JEL Classifications: Q41, Q47. DOI: https://doi.org/10.32479/ijeep.11351